Entrepreneurship, wealth, liquidity constraints and start-up costs - Raquel Fonseca; Pierre-Carl Michaud; Thepthida Sopraseuth (Institute for the Study of Labor (IZA), 2007)
We study the effects of liquidity constraints and start-up costs on the relationship between wealth and the fraction of entrepreneurs in an economy. We develop a dynamic occupational choice model with endogenous wealth and entry into entrepreneurship. The model predicts that, with liquidity constraints, the probability of entering entrepreneurship is an increasing function of individual wealth while the introduction of start-up costs tends to flatten this relationship. The theoretical predictions can be tested on cross-sectional data with exogenous variation in liquidity constraints (e.g. access to credit) and business start-up costs. We use three highly comparable micro datasets (SHARE, ELSA and HRS) providing harmonized data on wealth and work status in 9 countries that characterized by very different levels of start-up costs and liquidity constraints. Our results support our theoretical predictions. While higher liquidity constraints yield a positive relationship with wealth profile for the fraction of workers in entrepreneurship, start-up costs weaken this relationship by depressing the marginal value of being an entrepreneur as a function of wealth. Countries with high start-up costs such as Italy, Spain and France have flatter wealth gradients.
Keywords: 330; Berufswahl; Unternehmer; Vermögen; Unternehmensgründung; Kosten; Verschuldungsrestriktion; USA; Großbritannien; Deutschland; Schweden; Niederlande; Spanien; Frankreich; Italien; Dänemark